2016
DOI: 10.1002/cssc.201600289
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Carbon Dioxide Reduction at p‐Type Copper(I) Iodide

Abstract: A p-type semiconductor, CuI, has been synthesized, characterized, and tested as a photocatalyst for CO reduction under UV/Vis irradiation in presence of isopropanol as a hole scavenger. Formation of CO, CH , and/or HCOOH was observed. The photocatalytic activity of CuI was attributed to the very low potential of the conduction band edge (i.e., -2.28 V vs. NHE). Photocurrents generated by the studied material confirm a high efficiency of the photoinduced interfacial electrontransfer processes. Our studies show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 48 publications
(75 reference statements)
1
32
0
3
Order By: Relevance
“…In order to cope with the increasingly serious energy crisis, semiconductor photocatalysis has been considered as a prospective technique in response to the photocatalytic water splitting, carbon dioxide reduction, air pollutant removal, degradation of organic compounds and bacteria disinfection . To date, graphitic carbon nitride (g‐C 3 N 4 ), as a promising photocatalyst, has drawn considerable attention in these applications due to its appropriate band gap (2.7 eV), favorable chemical stability, zero toxicity and low cost.…”
Section: Introductionmentioning
confidence: 99%
“…In order to cope with the increasingly serious energy crisis, semiconductor photocatalysis has been considered as a prospective technique in response to the photocatalytic water splitting, carbon dioxide reduction, air pollutant removal, degradation of organic compounds and bacteria disinfection . To date, graphitic carbon nitride (g‐C 3 N 4 ), as a promising photocatalyst, has drawn considerable attention in these applications due to its appropriate band gap (2.7 eV), favorable chemical stability, zero toxicity and low cost.…”
Section: Introductionmentioning
confidence: 99%
“…Introduction Due to the contemporary energy shortage, CO2 conversion into chemical fuels through artificial photosynthesis has attracted much interest due to the massively available CO2 from industrial release. Although plenty of research has been focused on exploring efficient photocatalysts and co-catalysts for CO2 reduction, [1][2][3][4][5][6][7][8] the performance is still far from satisfied due to the difficulties in combining the suitable semiconductor with visible light response and the matched co-catalyst, especially controlling of electron transferring between them, as well as the CO2 affinity on to the active sites. [9] Graphitic carbon nitride (melon) is believed to be a promising semiconductor for CO2 reduction owning to its high conduction band.…”
mentioning
confidence: 99%
“…The improvement of CH 4 yield is ascribed to the emergence of copper foil as the electron sink where it retards the recombination rate of the electron-hole pairs. [22] Recent research has demonstrated that copper metal not only acts as a medium for electron transfer but also as an electron sink for the photogenerated electrons. [23] Consequently, when Bi 2 WO 6 is coupled with WO 3 , the CH 4 yield manifested a decrease to 3.45 μmol g À 1 catalyst .…”
Section: Resultsmentioning
confidence: 99%